Análise do comportamento dos tempos de produção em um sistema de manufatura flexível em um problema de escalonamento em um job shop: abordagem utilizando conceito de caminho crítico - Rodrigues, Antonio Gabriel (Universidade do Vale do Rio do Sinos, 2007)
In this work the Job Shop Scheduling Problem is studied, considering due dates, production turns and tooling constraints. This problem is applied in a Flexible Manufacturing System, which possesses high degree of automation, allowing previsibility in the processes of loading and unloading jobs on the machines. The problem is modeled through a objective function fn composed by three weighted decision variables. The importance of each variable in the fn final value is managed through assignment of values to the weights of these variables. In the proposed approach, it was used Group Technology and Tabu Search techniques. The implemented model is a modification of the i TSAB technique, proposed by Nowicki and Smutniki. The consideration of adicional constraints in the Job Shop Scheduling Problem increases the complexity of the implementation, otherwise, makes the problem closer to the industrial reality. The model was validated using benchmark instances, in which the data from the addional constraints were added.
Keywords: automação; busca tabu; computação; manufatura; manufatura flexível; processo; escalonamento; metaheuristic; flexible manufacturing system; group technology; tabu search; job shop scheduling problem; Ciências Exatas e da Terra